Biofortification of rice grain with zinc through zinc fertilization in different countries - N. Phattarakul (2018)
Background: Increasing zinc (Zn) concentration of rice seed has potential benefits for human nutrition and health. Enhanced levels of Zn in grain also contributes greatly to crop production through better germination and seedling vigor of rice plants grown on soils with limited Zn supply. Aims and methods: This study evaluated the effect of soil and/or foliar Zn fertilizer application on grain yield and grain Zn concentration of rice grown in 17 field trials conducted in 2008 to 2010 in China, India, Lao PDR, Thailand and Turkey on soils ranging in pH from 4. 8 to 8. 8 and DTPA- extractable Zn from 0. 5 to 6. 5 mg kg-1. Results: Zinc fertilization had little effect on rice grain yield with the exception of increases of up to 10 % in some locations in China and India. As an average of all trials, Zn application increased grain yield by about 5 %. Grain Zn concentrations were, however, more effectively increased by Zn fertilization, especially with foliar Zn applications. On average, Zn concentration in brown rice (whole caryopsis with husk removed) was increased by 25 % and 32 % by foliar and foliar + soil Zn applications, respectively, and only 2. 4 % by soil Zn application. The Zn concentration of un-husked rice (whole grain with husk), which was increased by 66 % by foliar Zn, showed a close association with the Zn in brown and white rice, indicating a possible penetration of Zn from the husk into the inner layers of the rice endosperm. Increase in grain Zn concentration by foliar Zn spray was significantly affected by the timing of the foliar application. More distinct increases in grain Zn by foliar Zn application were achieved when Zn was applied after flowering time, e. g., at early milk plus dough stages. Conclusions: Foliar Zn spray offers a practical and useful means for an effective biofortification of rice grain with Zn. This practice consistently and significantly contributed to increases in grain Zn of rice irrespective of cultivars, environmental conditions and management practices in 5 different countries. © 2012 Springer Science+Business Media B.V.